“The Pleasures in Being Seen”: An Interview with Dani Lessnau, Led by Drs. Stéfy McKnight and Julia Chan - Lessnau, Dani; McKnight, Stéfy; Chan, Julia (Surveillance & Society, 2024)
When conceptualizing the call for this special issue, one artist came to our (Julia and Stéfy’s) minds: Dani Lessnau. Her work straddles complexities of surveillance, voyeurism, desire, and female pleasure. In particular, we want to highlight Lessnau’s provocative performance photography series extimité created in 2017. Using a pinhole camera inserted into her vagina, she photographs the sexual intimacies and relationships with her partners. We ask more broadly, what does it mean to use surveillance as a method of pleasure? And, how can artists subvert or appropriate the surveillant gaze in ways that disrupt heteropatriarchy? We are grateful to have had the opportunity to explore these tensions and questions with the artist herself in this interview. Thank you, Dani, for engaging with us in this topic.